6 DIFFERENT WAYS TO BRIDGE THE LANGUAGE GAP (Scientific journal of the Fergana State University, 2025)
This article examines six methods of bridging linguistic gaps. Based on hermeneutic thinking, the internal and external characteristics of language are analyzed, and practical approaches to addressing gaps are presented. The study explores the use of borrowed words, metaphorical renaming, coding, word creation, back-formation, and polysemy as ways to fill existing gaps. The findings highlight the importance of linguistics in addressing linguistic gaps and emphasize factors contributing to the development of the Uzbek language.